Interannual Improvement in Sea Lettuce Blooms in an Agricultural Catchment - McGovern, Joseph V.; Nash, Stephen; Hartnett, Michael (Frontiers in Marine Science, 2019)
Riverine nutrient loading from agriculture is one of the most prominent pressures in the second cycle of river basin management planning for the European Union (EU) Water Framework Directive (WFD). Better farmyard nutrient management planning is the measure most likely to reduce agricultural nutrient loading to catchment watercourses and coastal receiving waters. The adjoining Argideen Estuary and Courtmacsherry Bay in the south west of Ireland drain a 150km2 catchment comprising mainly agricultural land. The receiving waters were allocated Poor ecological status under the WFD at the most recent appraisal. Subhourly water quality monitoring in the Timoleague River has been carried out by the Teagasc Agricultural Catchments Programme to track the changes in nutrient loading to the Argideen Estuary in response to improved farming practice. A biophysical model of the adjoining Argideen Estuary and Courtmacsherry Bay was calibrated and Six nutrient load scenarios were simulated to determine their impact upon macroalgae and phytoplankton bloom magnitude. In addition, nutrient flow-load relationships were derived for summers 2010 and 2016 to elucidate the improvements induced by better catchment management practice. Flow-load relationships for dissolved inorganic nitrogen (DIN) and dissolved inorganic phosphorus (DIP) for each year were applied to the flow data for the other year, to query the outcome if 1) there had been no change in farm management practice between 2010 and 2016, or 2) the improved farm management practice in place by 2016 had been implemented by 2010. The difference between expediting and delaying improvement in farm nutrient management practice was a 5% increase in DIN loading and a 233% increase in DIP load. Application of this higher estimated load to the calibrated bio-physical model projected an increase in 2016 Ulva bloom magnitude from 381t to 1,391t. Although phosphorus retention within the catchment has improved in recent years, with an attendant improvement in Ulva bloom magnitudes, flow connectivity in the catchment still facilitates a higher phosphorus transfer during large rainfall events. A high amount of phosphorus is stored within the catchment, while point source pressures continue to contribute to phosphorus transfer to streams during periods of low flow.